Effect of gamete aging on fertilization success of the sea urchin Arbacia dufresnii (Arbacioida: Arbaciidae) - Fernández, Jimena Pía; Di Marco, Florencia; Rubilar, Tamara; Cledón, Maximiliano; Gonzalez Pisani, Ximena (Revista de Biología Tropical, 2024)
Introduction: Short-term gametes storage is an inexpensive and simple technique that allows the use of the same batch of eggs or sperm at different times, maximizing the application of research protocols and the use of gametes in production. Arbacia dufresnii is a sea urchin species with proven aquaculture potential and already used in the nutraceutical industry. Aging of its gametes is unknown and is a needed information to scale up the production. Objective: Determine the effect of male and female gamete aging on the fertilization success of Arbacia dufresnii. This will allow optimizing the use of gametes after collection decoupling spawning from fertilization. Methods: A. dufresnii individuals were induced to spawn and gametes were kept at 12 ± 1 °C throughout each bioassay. Sperm was separated into two treatments: activated sperm in seawater (AS), and dry sperm (DS). Two bioassays were made: Bioassay 1 evaluated the effect of time on fertility by performing fertilization tests at 0 h, 24 h, 48 h, 72 h, and 96 h after spawning. Bioassay 2 evaluated the contribution of each type of aged gamete on fertility, combining aged gametes (96 h) with fresh gametes (0 h). Results: Bioassay 1: the fertilization success obtained by combining eggs (E) with AS or DS presented important differences. While the fertilization success remained acceptable (greater than 50 %) for up to 72 h using ExDS, it only remained acceptable for up to 48 h using ExAS. Bioassay 2: acceptable fertilization success was found by combining aged E (96 h) with fresh sperm, or aged DS (96 h) with fresh E, but not using aged AS with fresh E. Conclusions: The findings of this work show that fertilization success in A. dufresnii gametes remains relatively unchanged for up to 48 h after spawning when combining ExAS, and for up to 72 h when combining ExDS. However, when combining aged E or aged DS with a fresh gamete, post-collection fertilization can be extended up to 96 h. In this work, the first steps have been taken to understand the conservation time of A. dufresnii gametes with minimum intervention.